2013
DOI: 10.1007/s10555-013-9461-5
|View full text |Cite
|
Sign up to set email alerts
|

The promise of sonodynamic therapy

Abstract: Sonodynamic therapy is a potential cancer treatment modality that has been gaining support due to its effectiveness in both in vitro and in vivo studies. The therapeutic method combines ultrasonic irradiation with drugs known as sonosensitizers that amplify its ability to inflict preferential damage on malignant cells. This is based on the idea that ultrasonic waves have the ability to exhibit profound physical and chemical changes on cellular structure. The mechanisms by which ultrasound (US) disrupts cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 32 publications
1
146
0
2
Order By: Relevance
“…We have shown that zebrafish can be safely sonicated using pulsed low frequency ultrasound (20 kHz), and that their tolerance to chemotherapeutic agents is quantitatively comparable to doses tolerated by murine models 26 , suggesting that tumor-bearing zebrafish may be used in preliminary investigations to assess the in vivo antineoplastic activity of these protocols. Nevertheless, administering chemotherapeutic agents prior to sonication of mammalian models has been reported in the MHz range 1 , and such protocols can likely be extended to incorporate low frequency ultrasound, as well as cholesterol-depleting and cytoskeletal-directed agents.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that zebrafish can be safely sonicated using pulsed low frequency ultrasound (20 kHz), and that their tolerance to chemotherapeutic agents is quantitatively comparable to doses tolerated by murine models 26 , suggesting that tumor-bearing zebrafish may be used in preliminary investigations to assess the in vivo antineoplastic activity of these protocols. Nevertheless, administering chemotherapeutic agents prior to sonication of mammalian models has been reported in the MHz range 1 , and such protocols can likely be extended to incorporate low frequency ultrasound, as well as cholesterol-depleting and cytoskeletal-directed agents.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Ultrasound refers to any oscillating sound pressure wave with a frequency greater than the upper limit of human auditory capacities (~ 20 kHz) 1 . Low frequency ultrasound in the 20-60 kHz range has been utilized in the laboratory as a means of generating emulsions, preparing cellular samples for nucleic acid extraction, for tissue disruption, and for a variety of other tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…i.e., light's relatively limited capacity to penetrate human tissue [34,35]. Noteworthy is the fact that attention is now increasingly focused towards the possibility of enhancing the cancerspecific immunity upon direct ultrasound-induced treatment [35,13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the mechanical characteristics of ultrasound waves, changing pressure gradients in liquid leads to the growth, oscillation, and/or collapse of gaseous cavities (bubbles) [13]. Cavitation can be typically observed into two types as stable and inertial, which are regulated by the oscillatory behavior of bubbles under acoustic field [13][14][15][16]. Stable cavitation could be identified with the periodic oscillations of gas bubbles that have already existed in the tissue and that could be observed as the waxing bubble during the negative pressure half cycle and the shrinking bubble during the positive pressure half cycle as response to an ultrasound wave field [9,13,17,18].…”
Section: Introductionmentioning
confidence: 99%